Dynamics of Influenza A (H5N1) virus protein sequence diversity - Abd Raman, Hadia Syahirah; Tan, Swan; August, Joseph Thomas; Khan, Asif M.; KHAN, MOHAMMAD ASİF (My University, 2020)
Background. InfluenzaA(H5N1) virus is a global concern with potential as a pandemic threat. High sequence variability of influenza A viruses is a major challenge for effective vaccine design. A continuing goal towards this is a greater understanding of influenza A (H5N1) proteome sequence diversity in the context of the immune system (antigenic diversity), the dynamics of mutation, and effective strategies to overcome the diversity for vaccine design.